Illness perception and social support among cardiac patients attending rehabilitation programme and their experiences / Sukhbeer Kaur Darsin Singh - Sukhbeer Kaur, Darsin Singh (2021)
Cardiovascular disease (CVD) and coronary heart disease (CHD) have emerged as the leading causes of death in Malaysia. In developed countries, heart disease is the leading cause of death in men and women in Europe, CHD accounts for an estimated 1.95 million deaths each year. In Europe, according to the World Health Organisation (WHO 2012), it is recorded that 42 percent of deaths were caused by CVD and 41 percent was by CHD which was 2,655,364 people has died. Secondary prevention through cardiac rehabilitation (CR) is a key component of the ongoing care of these patients, immediately following discharge from hospitals. Despite being an important secondary prevention programme the individual participation and utilization towards this programme remain low. The primary objective of the present study was to determine the illness perception (BIPQ), social support (ESSI), and the factors associated with the demographic and clinical history of the participants that have attended cardiac rehabilitation programme. The secondary objective was to explore the attendeesï¿½ experiences attending this programme. Mixed-methods research using the embedded design was conducted to address the research objectives. A quantitative approach utilizing the longitudinal survey was employed and was supported by the qualitative study. A convenience sample of four hundred and fifty participants was conveniently selected. Brief Illness Perception Questionnaire (BIPQ) and the ENRICHD Social Support Instrument (ESSI) were tested for reliability and used to collect data. BIPQ and ESSI were used at the baseline before the cardiac rehabilitation programme (CRP) at Phase I during hospitalization on basic information on diet, physiology of the disease and, general exercise) before the 4 th (T1) and 8th sessions (T2) of CRP Phase II (exercise intervention). Descriptive statistics included frequency distribution, mean standard deviation was employed to summarize the data, Chi-Square was used to determine any association while inferential statistics; Repeated measures of ANOVA and Logistic Regression were applied to analyse the data. iv Meanwhile, thematic analysis was employed to analyze qualitative data of the semi?structured transcripts. Fifteen participants were recruited purposively for a semi?structured in-depth interview to explore their perceptions towards CRP. The quantitative findings for illness perception (BIPQ) were statistically significant among cardiac participants but there were no significant changes for social support (ESSI) scores during their attendance at the CRP intervention at the 4th and 8th session CRP. The predictors for BIPQ at the 8th session of CRP were; had a previous cardiac history of AMI (OR=2.380, 95%CI 1.46, 5.49), had angioplasty with stent (OR=3.857, 95%CI 1.55, 9.61). The predictors for ESSI at the 8th session were; a previous cardiac history of AMI (OR=3.050, 95%CI 1.71, 5.43), with the previous history of open-heart surgery (OR=2.442, 95%CI 1.36, 4.40). The qualitative findings resulted in three themes emerging including benefits, barriers, and reminders from staff. Nine subthemes emerged from the main themes including knowledge, motivation, socialization, timing, facilities, financial, reminders by the hospital, family support, and spouse encouragement. In conclusion, illness perception scores changed during the attendance of the cardiac participants to CRP at the 4th and 8th sessions but no changes were found for social support. Previous cardiac history of AMI and having open heart surgery done were the predictors for illness perception and social support and themes on knowledge, barriers and reminders from the hospital were the emerged themes from the qualitative aspect. Therefore, participants perceived their illness beliefs positively during their attendance for CRP and, themes obtained supported the quantitative findings. Therefore, the participants appreciated the cardiac rehabilitation programme and thus nurses should encourage and motivate participants to attend CRP. Keywords: illness perception, social support, cardiac rehabilitation programme, cardiac patients